Effects of human urine application on soil physicochemical properties, microbial communities, and enzymatic activities - Yu, Guangquan; Wang, Qian; Zheng, Xiangqun; Yang, Bo; Zhang, Chunxue; Zhang, Guowei; Wei, Xiaocheng (Frontiers in Agronomy, 2025)
Human urine (HU) is rich in nutrients necessary for plant growth, and recycling HU as fertilizer has multiple positive impacts, such as enhancing agricultural sustainability, reducing wastewater pollution, and decreasing reliance on chemical fertilizers, so it is of great significance to explore the effects of urine agricultural utilization on soil environment. A pot experiment was conducted to evaluate the impacts of varying HU application rates {0 [control (C)], 13, 26, 52, and 104 mL kg−1} on soil physicochemical properties, microbial communities, and enzymatic activities. The findings indicate that HU application enriched soil nutrients and significantly increased soil electrical conductivity, with levels at 104 mL kg−1 reaching an increase of 840% over C. Compared to the C, HU enhanced the activities of soil enzymes such as invertase, urease, and catalase by 7.30%–58.75%, 0.93%–47.77%, and 1.56%–16.62%, respectively, but reduced alkaline phosphatase activity by 6.40%–64.76%. Additionally, increasing HU application was correlated with reductions in both operational taxonomic units and the Shannon–Wiener diversity index. The relative abundance of soil bacteria such as Pseudomonadota and Gemmatimonadota incrementally rose with higher HU input, whereas that of Bacillota declined. Moreover, the composition of the top 20 bacterial genera, including Gaiella (1.49%), Bacillus (1.47%), and Blastococcus (1.02%), was significantly altered by HU application. In conclusion, HU application changes the soil ecological environment and, to some extent, modifies the structure and diversity of soil bacterial communities and enzymatic function. However, the absence of long-term field trials underlines the necessity for comprehensive evaluations of HU’s impact on soil fertility and crop health, and careful attention must be paid to potential environmental safety risks post-HU application.